Radion and Higgs signals in peripheral heavy ion collisions at the LHC - Lietti, S. M.; Roldao, C. G. (Elsevier B.V., 2002)
We investigate the sensitivity of the heavy ion mode of the LHC to Higgs boson and Radion production via photon-photon fusion through the analysis of the processes gammagamma --> gammagamma, gammagamma --> b (b) over bar, and gammagamma --> gg in peripheral heavy ion collisions. We suggest cuts to improve the Higgs and Radion signal over standard model background ratio and determine the capability of LHC to detect these particles production. (C) 2002 Elsevier B.V. B.V. All rights reserved.